Fabrication and energy harvesting characteristics of unimorph piezoelectric cantilever generators with interdigitated electrode lead zirconate titanate laminates. (16th November 2017) - Lee, Min-seon; Yun, Ji-sun; Park, Woon-ik; Hong, Youn-woo; Cho, Jeong-ho; Paik, Jong-hoo; Park, Yong Ho; Son, Chun-myung; Jeong, Young Hun
Abstract: Interdigitated electrode (IDE) unimorph piezoelectric cantilever generators (UPCGs) were fabricated and their energy harvesting characteristics were investigated. A hard lead zirconate titanate (PZT) material with a high mechanical quality factor ( Q m ) of 1280 was used for the active piezoelectric film of the IDE UPCGs. Two different laminated IDE UPCGs were prepared; one has Ag/Pd interdigitated electrode (IDE) formed only on the top and bottom PZT sheets (D-IDE), while the other has Ag/Pd IDE on all of the PZT sheets (M-IDE). Cofiring was conducted at 1050 °C for 2 h for PZT laminates with IDEs. The fabricated IDE UPCGs exhibited power densities of 50.4 µW/cm 3 for the D-IDE and 820 µW/cm 3 for the M-IDE. The UPCG with the M-IDE exhibited a higher performance than that with the D-IDE. Specifically, a significantly enhanced normalized power factor of 670 µW/(g 2 ·cm 3 ) was found at 118 Hz across 100 kΩ.